2021
DOI: 10.1007/s10803-021-05089-3
|View full text |Cite
|
Sign up to set email alerts
|

Empathic Accuracy in Adolescent Girls with Turner Syndrome

Abstract: To examine the potential mechanisms underlying social deficits in Turner Syndrome, we administered the empathic accuracy task (EAT) -a naturalistic social cognition task- and a (control) visual-motor line-tracking task to 14 girls with TS was compared to 12 age-matched typically developing girls (TD; ages 12 to 17). Empathic accuracy was compared across positive and negative emotionally valanced videos. We found that TS differs from TD on empathic accuracy ratings for negative videos; no differences were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In our sample, few studies investigated age as a predictor of EA, instead evaluating the correlation between age and EA. Among the five studies investigating age as a correlate of EA in older children and adolescents, age was not a predicting factor of EA in Castro et al (2015), Haugen et al (2008), nor Klabunde et al (2021). However, when comparing three samples of typically developing adolescents, adolescents with attention deficit hyperactivity disorder, and adolescents with autism spectrum disorder, Demurie et al, (2011) found a positive correlation between age and EA only for the autism spectrum disorder group.…”
Section: Variation In Ea During Childhood and Adolescencementioning
confidence: 87%
See 1 more Smart Citation
“…In our sample, few studies investigated age as a predictor of EA, instead evaluating the correlation between age and EA. Among the five studies investigating age as a correlate of EA in older children and adolescents, age was not a predicting factor of EA in Castro et al (2015), Haugen et al (2008), nor Klabunde et al (2021). However, when comparing three samples of typically developing adolescents, adolescents with attention deficit hyperactivity disorder, and adolescents with autism spectrum disorder, Demurie et al, (2011) found a positive correlation between age and EA only for the autism spectrum disorder group.…”
Section: Variation In Ea During Childhood and Adolescencementioning
confidence: 87%
“…Regarding the objectives of the studies, 11 studies evaluated the link between EA and other variables (e.g., age, parental characteristics, gender). Ten studies compared groups of subjects based on different variables, such as clinical conditions (Demurie et al, 2011;Klabunde et al, 2021;Martin-Key et al, 2017;Martin-Key et al, 2020;Vilas et al, 2021), intervention (Goldstein & Winner, 2012;Kral et al, 2018), age (Kunzmann et al, 2018), and school bullying (Franzen et al, 2021). Finally, Braun and von Oertzen (2021) evaluated contextual differences in a within-subject design by testing how the presence of a mentor enhanced EA in adolescents when talking about an emotional subject.…”
Section: Studies Characteristicsmentioning
confidence: 99%